Impoliteness Strategies Used by White Males and Females toward the Black Staff in The Hidden Figures Movie - Aveline Catriona (Institute of Research and Community Outreach - Petra Christian University, 2023)
This qualitative research was done to find the types of impoliteness strategies used by the white characters in the Hidden Figures movie (Al Harisson, Paul Stafford, Vivian Mitchell, and Ruth), and how the recipient of impoliteness, Katherine Johnson (a black character), responded to it. The main theory used is Culpeper's (1996, 2003) impoliteness strategy and Bousfield’s (2008) responses to impoliteness. The findings revealed that not every impoliteness strategy was produced by the characters. The one strategy that was not produced is withhold politenessbecause there were no such silent scenes in the movie. Besides withhold politeness, every type of impoliteness strategy was produced in the Hidden Figures movie. In addition, Katherine Johnson produced two types of responses to Al Harisson and Paul Stafford: accepting face attack and countering face attack. While responding to Vivian Mitchell and Ruth, Katherine Johnson only produced one type of response: accepting face attack. In conclusion, in this research impoliteness strategies and the responses were used in the Hidden Figures movie. In addition, impoliteness could occur due to job status and race factor.